(untitled) (MAGNETON: Jurnal Inovasi Pembelajaran Fisika UNWIRA, 2026)
This study analyzes the quality of physics learning videos on the YouTube platform, focusing on pedagogical aspects, interactivity, visualization, conceptual clarity, and content suitability based on specific learning models. Using a document analysis method applied to videos implementing Problem-Based Learning and active learning models, the study found that these videos are effective in enhancing students’ conceptual understanding, critical thinking, and creativity through the integration of real experiments and in-depth data analysis. However, it was highlighted that interactive elements are often minimal, leading to passive learning experiences. Therefore, it is recommended for video designers to enhance interactive components such as quizzes and discussions, and to ensure adequate technical video quality to maximize student engagement and learning effectiveness. The findings of this research are expected to serve as a reference for media developers in creating more innovative and effective physics learning videos.